Computational Intelligence in Analog and Mixed-Signal (AMS) and Radio-Frequency (RF) Circuit Design - Fakhfakh, Mourad; Tlelo-Cuautle, Esteban; Siarry, Patrick (Springer International Publishing : Imprint: Springer, 2015)
Long considered a "black art", designers of digital, analog, radio-frequency and mixed-signal systems are now looking to means for automating the design flow of electronic circuits using new, computationally intelligent approaches, based on modeling, synthesis, design methodologies, optimization algorithms, and metaheuristics. This book explains the application of recent advances in computational intelligence - algorithms, design methodologies, and synthesis techniques - to the design of integrated circuits and systems. It highlights new biasing and sizing approaches and optimization techniques and their application to the design of high-performance digital, VLSI, radio-frequency, and mixed-signal circuits and systems. This first of two related volumes addresses the design of analog and mixed-signal (AMS) and radio-frequency (RF) circuits, with 17 chapters grouped into parts on analog and mixed-signal applications, and radio-frequency design. It will be of interest to practitioners and researchers in computer science and electronics engineering engaged with the design of electronic circuits.